NEOMYTHOLOGICAL TENDENCIES IN CONTEMPORARY PROSE: STORIES BY LEV NAUMOV - V A Gavrikov (RUDN Journal of Studies in Literature and Journalism, 2016)
This article is devoted to neomyphological aspects of the creative work of contemporary writer Lev Naumov. It includes a brief overview of his biography and key artistic achievements. In the research dominant attention is paid to the specifics of Naumov’s creative method, which can be determined as metaphysical parables, philosophical prose with the elements of science fiction and metanarration. Article proves that stories from the author’s book “Whisper of Forgotten Letters” represent a solid supertext, in which the neomyphological tendencies are strong and vital. These tendencies are notable in the arrangement of the space-time continuum, subjectival area and plots composition. Matrix semantic structure of Naumov’s texts is arranged by sacred codes, which have typological affinity with texts of protoreflective traditionalism. At the same time, there are traces of postmodern game poetics in author’s texts.